Smartphone usage on senior citizen - fithri, hidayah kariima; Rifani, Jeanny Indra; Aniendya, Mutyara Whening; Jamilah, Nadiratin; ghosh, anusua (Association for Scientific Computing Electrical and Engineering, 2020)
The impact of the digital era is the gap between active smartphone users and those who are not particular. Then IT is not fully felt by the senior citizen. This study aims to determine the ability of the senior citizen in the use of smartphones. The results of the study will be used as a reference for teaching IT to four senior citizen people. As a result, two senior citizen people want to be taught to use smartphones intensive and privately.